Peran Dividen dalam Memoderasi Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan - Sari, Fitri Indah Mayang; Yamasitha (Riset Sinergi Indonesia, 2025)
This research aims to examine the influence of Profitability, Leverage and Free Cash Flow on Company Value with Dividend Policy as a Moderating variable in Consumer Goods Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2019 - 2023. Sampling was used using the Purposive Sampling method and 24 companies were selected as research samples. The data analysis technique used is Multiple Linear Regression analysis and Moderated Regression Analysis (MRA) with SPSS Statistics 21 tools to test the hypothesis. Research results using multiple linear regression analysis show that Profitability and Leverage have a positive and significant influence on Company Value, while Free Cash Flow has an insignificant effect on Company Value. Research results using Moderated Regression Analysis (MRA) show that Dividend Policy can moderate the influence of Profitability and Free Cash Flow on Company Value, but cannot moderate the influence of Leverage on Company Value.